Surface Coatings—2
X, 230 p.
Keywords: The science and technology of surface coatings continues to advance. Among the key areas are polymer chemistry, as new binders are developed to meet increasingly stringent environmental demands; testing and evaluation, as the need to understand the factors affecting coatings performance becomes ever more intense; and studies of that enduring problem, corrosion of metal substrates, from which coatings of ever improving effectiveness are emerging. We have in this present volume of the series continued to cover aspects of these numerous developments. There are chapters on waterborne paint, a subject of increasing environmental importance, by J. W. Nicholson, and by H.-J. Streitberger and R. P. Osterloh; on a new and sophisticated test method, acoustic emission (R. D. Rawlings); and on anticorrosion coatings both organic (W. Funke) and inorganic (M. C. Andrade and A. Macias). Finally, that topic of immense practical importance to paint technology, pigmentation, is covered in a chapter by the late T. Entwistle. All the authors have brought considerable experience in their chosen field of coatings technology to the preparation of their chapters, all of which are timely reviews of developing topics. We are grateful to each author for helping in the preparation of this volume, and for putting their experience at the disposal of the wide audience for whom this book is intended.